T Regulatory and T Helper 17 Cells in Primary Sjögren’s Syndrome: Facts and Perspectives - Alessia Alunno; Francesco Carubbi; Onelia Bistoni; Sara Caterbi; Elena Bartoloni; Giulia Mirabelli; Francesca Cannarile; Paola Cipriani; Roberto Giacomelli; Roberto Gerli (Mediators of Inflammation)
Historically, primary Sjögren’s syndrome (pSS) was thought to be a T helper (h) 1 driven disease due to the predominance of CD4+T lymphocytes and their products in target organs and peripheral blood of patients. In the last decades, the identification of a number of T cell subsets, including Th17, T regulatory (Treg), and follicular helper T cells, challenged this long-standing paradigm and prompted to identify their role in pSS pathogenesis. In addition the impact of abnormal proinflammatory cytokine production, such as IL-6, IL-17, IL-22, and IL-23, has also attracted considerable attention. However, although several studies have been carried out in experimental models and patients with pSS, many aspects concerning the role of Treg cells and IL-17/Th17 cell system in pSS pathogenesis are not fully elucidated. In particular, the role played by different IL-17-producing T cell subsets as well as the effects of pharmacological therapies on Treg/Th17 cell balance represents an intriguing issue. The aim of this review article is to provide an overview of current knowledge on Treg cells and IL-17-producing T cells in pSS pathogenesis. We believe that these insights into pSS pathogenesis may provide the basis for successful therapeutic intervention in this disease.